Ahmadiyya Community In Indonesia’s Contemporary Discourse: State’s Indecisive Protection to the Freedom of Religion and Belief - Putri, Pradnya Nindita (International Journal of Social Service and Research, 2023)
Nowadays, Indonesian Ahmadiyya community is the religious minority group with highest number and level of prohibition regulations and persecution. Several studies already shown that this situation was triggered by the 2005 fatwa published by Indonesian Ulema Council (Majelis Ulama Indonesia – MUI) which declared the Ahmadiyya as deviant sect and that seemed to be confirmed by the State through the issuance of Joint Decree of 3 Ministers (SKB 3 Menteri) no 3 of 2008 concerning Warnings and Orders to Adherents, Members, and/or Members of the JAI Management and the Community. More than a decade after the issuance of the fatwa and decree, current Minister of Religion that appointed in December 2020, Yaqut Cholil Choumas, stated his desire to affirm the Ahmadiyya’s rights as citizens. In fact, this statement did not stop the persecution experienced by the Ahmadis, as what happened in Sintang District in September 2021. This study highlights that inappropriate State intervention in religious affairs has become one of the triggers that perpetuate the discrimination against minority groups. Along with this reason, this study attempts to examine the State’s narrative on Ahmadiyya’s issue through critical discourse analysis developed by Teun A. van Dijk (1993). This study finds that the State contributes to perpetuating discrimination against minority groups because it provides half-hearted protection for the Ahmadiyya community by placing the values of certain religious beliefs as well as harmony and public order as being more important than freedom of religion and belief.